The Contributions of Principals Leadership and Climate’s School to Performance of Teachers Elementary School at Kecamatan Kandis Kabupaten Siak - Jufrianti Jufrianti; Syahril Syahril; Yahya Yahya (CV. AFDIFAL MAJU BERKAH, 2023)
This research was based on a case where the result of observation by researcher in Elementary School at Kecamatan Kandis Kabupaten Siak that showed the low level of teacher performance. Many factors affected the teacher performances which are principal’s leadership and climate school. The purpose of this research are to know about: (1) contribution of principals leadership to teacher performance, (2) contribution of climate school to teachers performance, and (3) contribution of principals leadership and climate school are jointly to teachers performance. The method of this study is quantitative research with sample are 76 teachers at Elementary School in Kecamatan Kandis Kabupaten Siak. Sample in this research has taken by stratified proportional random sampling method. Instrument in this research using questionnaire. The results of the analysis data show that (1) principals leadership contributes significantly to teachers of 15.8%, (2) climate school contributes significantly to teachers of 50.9 %, and (3) principal’s leadership and climate school make a significant contribution to teachers performance of 54%, so the conclusion of this research are that hypothesis acceptable empirically and principal’s leadership and climate school variable are two factors that contribute to the teacher performance and 46% of the remaining influence by another factors.